AlN/GaN-Based MOS-HEMT Technology: Processing and Device Results - S. Taking; D. MacFarlane; E. Wasige (Active and Passive Electronic Components)
Process development of AlN/GaN MOS-HEMTs is presented, along with issues and problems concerning the fabrication processes. The developed technology uses thermally grown Al2O3 as a gate dielectric and surface passivation for devices. Significant improvement in device performance was observed using the following techniques: (1) Ohmic contact optimisation using Al wet etch prior to Ohmic metal deposition and (2) mesa sidewall passivation. DC and RF performance of the fabricated devices will be presented and discussed in this paper.